IDENTIFICATION AND EVALUATION OF ENVIRONMENTAL IMPACTS: A CASE STUDY - Cruz, Franciane Cougo da; Cruz, Anderson Cougo da; Rossato, Marivane Vestena (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The environmental issue has acquired social and political dimension mainly from the late 60. Such a situation has been observed precisely because man seeks only the immediate benefits of their actions, favoring economic growth to at any cost and relegating the the background, the ability to recovery ecosystems. In this context, emerges the need to generate development without disregarding meet the needs of current and future society, as well as to ensure improved quality of life. Thus, based on the theme of sustainability and environmental management, this research aimed to identify and evaluate potential environmental impacts associated with the illegal occupation of the banks of the Arroyo Bage, stream located in the city of Bage/RS. To do so, we developed a case study through a research of a qualitative, exploratory and descriptive, using, for this purpose, the technique of network interaction. With the study, a number of environmental impacts, such as the change of the local flora and fauna. Highlights the need for greater attention to solving the identified environmental problems and it is evident that preventive and mitigating actions can reduce the impacts already caused, thereby decreasing the negative consequences and maximize local potential.